Comparative Techno-Economic and Exergetic Analysis of Circulating and Dual Bed Biomass Gasification Systems - Silva Ortiz, Pablo; Maier, Simon; Dietrich, Ralph-Uwe; Pinto Mariano, Adriano; Maciel Filho, Rubens; Posada, John (Frontiers in Chemical Engineering, 2021)
In this work, the techno-economic and exergy analyses of two gasification technologies with integration into heat and power combined cycles are presented: i). Circulating fluidized bed (CFB), and ii). Dual fluidized bed (DFB) systems. As feedstock, lignocellulosic biomass (sugarcane bagasse, SCG) was considered. The gasification process of the fluidized-bed systems (circulating and dual bed) and the syngas conversion were performed using Aspen Plus® software. The process design includes biomass drying and gasification, syngas cleaning, combustion, power generation, and heat recovery. The SCB-DFB system has the lowest irreversibility rate and, as a result, the highest overall performance and power generation (achieving 32% in the gasification system and 53% of exergy efficiency when coupled with the combined cycle). From the techno-economic assessment, the SCB-DFB system has the lowest total production costs per unit of energy. Hence, the dual fluidized bed systems could be a more competitive technology for the agro-industrial sector to generate power from lignocellulosic materials.